Assessing citizens' demographic attributes on satisfaction and confidence level during Malaysian movement control order - Mohd Amin, Siti Hajjar; Abdullah, Aida; Mohamed Ali, Abdul Jalil; Mohd Shafie, Siti Aishah; Mohd Wahid, Siti Daleela (Faculty of Administrative Science and Policy Studies, 2023)
This study investigates the satisfaction and confidence level of Malaysian citizens through demographic characteristics. A cross-sectional survey of 346 Malaysian citizens uses snowball sampling until it reaches the appropriate sample size. For data analysis, the Statistical Package for Social Science (SPSS) software, such as the Kolmogorov-Smirnov Test for Normality and Kruskal-Wallis One-Way Analysis for non-parametric data, to test the significant difference between the demographic groups for satisfaction and confidence level. Finally, the Mann-Whitney test was used for further analysis to test for a significant difference between all the possible pairs of groups. This study's finding revealed a significant median difference in citizens' satisfaction and confidence level in overall government performance during the COVID-19 outbreak based on marital status, level of education, and sector concurrently to each pair of the segments. Based on the findings, future studies might consider using probability sampling and thus be able to conduct parametric analysis.